Submasseteric abscess: an unusual head and neck condition - Razali, Mohd Sayuti; Abdullah, Baharudin; Muhammad, Amran (Universiti Sains Malaysia, 2007)
Submasseteric abscess is unusual in the head and neck region. Patients with this condition may be misdiagnosed as a parotid abscess due to the similarities in their presentation. Awareness and due recognition should be given to this unusual problem.